2017
DOI: 10.18203/2394-6040.ijcmph20172819
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pregnancy-induced hypertension in block Hazratbal of district Srinagar, Jammu and Kashmir: a prospective longitudinal study

Abstract: Background: The term pregnancy induced hypertension (PIH) suggests a disorder of blood pressure that arises because of the pregnancy. PIH is defined as new onset hypertension with or without significant proteinuria emerging after 20 weeks of gestation, during labour, or in first 48 hours post-partum. It is classified as gestational hypertension (without proteinuria), preeclampsia (with proteinuria), and eclampsia (associated with convulsions). Incidence of PIH varies from country to country and has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A study conducted in block Hazratbal of district Srinagar in Kashmir valley found out the prevalence to be 20%. 8 Another study conducted in block Hajin of district Bandipora of Kashmir valley found out the prevalence to be 7.4%. 9 A systematic review by Dhinwa et al which included a total of 18 studies with 92,220 study participants found that the pooled prevalence of PIH in India was 11%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study conducted in block Hazratbal of district Srinagar in Kashmir valley found out the prevalence to be 20%. 8 Another study conducted in block Hajin of district Bandipora of Kashmir valley found out the prevalence to be 7.4%. 9 A systematic review by Dhinwa et al which included a total of 18 studies with 92,220 study participants found that the pooled prevalence of PIH in India was 11%.…”
Section: Discussionmentioning
confidence: 98%
“…Based on a prevalence of 20% as per a study conducted in Block Hazratbal, and taking a non response rate of 20%, a minimum sample size of 295 was calculated but finally a sample of 402 was achieved. 8…”
Section: Sample Sizementioning
confidence: 99%
“…in their community-based study conducted in Hazratbal (Srinagar) reported the incidence of PIH to be 20%. [ 12 ] A community-based study done in Chiri, Haryana, conducted by Mehta B et al . reported the prevalence of hypertension in pregnancy to be 6.9%.…”
Section: Discussionmentioning
confidence: 99%